Anti-CRISPR proteins function through thermodynamic tuning and allosteric regulation of CRISPR RNA-guided surveillance complex. Issue 19 (10th October 2022) - Patterson, Angela; White, Aidan; Waymire, Elizabeth; Fleck, Sophie; Golden, Sarah; Wilkinson, Royce A; Wiedenheft, Blake; Bothner, Brian
Abstract: CRISPR RNA-guided detection and degradation of foreign DNA is a dynamic process. Viruses can interfere with this cellular defense by expressing small proteins called anti-CRISPRs. While structural models of anti-CRISPRs bound to their target complex provide static snapshots that inform mechanism, the dynamics and thermodynamics of these interactions are often overlooked. Here, we use hydrogen deuterium exchange-mass spectrometry (HDX-MS) and differential scanning fluorimetry (DSF) experiments to determine how anti-CRISPR binding impacts the conformational landscape of the type IF CRISPR RNA guided surveillance complex (Csy) upon binding of two different anti-CRISPR proteins (AcrIF9 and AcrIF2). The results demonstrate that AcrIF2 binding relies on enthalpic stabilization, whereas AcrIF9 uses an entropy driven reaction to bind the CRISPR RNA-guided surveillance complex. Collectively, this work reveals the thermodynamic basis and mechanistic versatility of anti-CRISPR-mediated immune suppression. More broadly, this work presents a striking example of how allosteric effectors are employed to regulate nucleoprotein complexes.